Peran Artificial Intellegence bagi Jurnalis Kediripedia.com dan Implementasi Relevansi Nilai-Nilai Islam - Ellyda Retpitasari; Fairizal Rahman (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The development of technology in the world has led to a new transformation in the form of artificial intelligence technology, commonly known as artificial intelligence (AI). The presence of AI is certainly a challenge for media actors or journalists, it can be able to facilitate but also pose a threat. The purpose of this research is to examine the role of AI for Kediripedia Journalists. Research on the use of artificial intelligence for Kediripedia.com journalists uses descriptive qualitative research methods. In this case, qualitative data is realized through descriptive sentences, and in-depth explanations through the process of data collection techniques from observation, interviews, and documentation. The results of the study state that AI plays an important role in the news production process, but in reporting news to Kediripedia journalists still prioritize good values, as required by Islam such as providing good and correct news information, as a unifier of society or not reporting that tends to divide society, and upholding Islamic values according to the Islamic syiar that was recommended by the Prophet Muhammad SAW.